Electric-Based Vehicle Control System with Modified Half-Wave Rectifier Circuit to Increase Battery Power Efficiency - Firmansah, Arif; Mulyadi, Adi (Fakultas Teknik Universitas PGRI Banyuwangi, 2023)
This paper discusses electric-based vehicle control systems. Electric vehicle charging stations are only capable of charging based on slow, medium, fast, ultra fast charging and are not equipped with an overcharge system. So a control system is proposed for overcharge protection of battery current and voltage. The control system is modified with a half wave rectifier circuit to increase battery power efficiency. Method of modifying a half wave rectifier circuit with IC LM 7812 and capacitor. The results of the circuit modification show that the battery power is 7.96 w, 7.26 w, 6.60 w, 5.94 w, 5.24 w at varying input voltages of 220-200 Vac, and the efficiency is 0.87%-0.86% at an input voltage of 190-180 Vac. Meanwhile, the battery power is 7.96 w at an input voltage of 230 Vac and the efficiency is constant at 0.87%. The application of a control system can increase the efficiency of electricity-based vehicle batteries at a constant input voltage.